Historical Meme As a Solution to Improve Generation Z Nationalism in Indonesia - Febri Choiru Rozikin (HISTORIA : Jurnal Program Studi Pendidikan Sejarah, 2021)
The development of the world of technology brings various influences on society. This progression includes communication between members. Generation Z as a generation that has grown up together with technological developments faces a formidable challenge. The threat of nationalism identity erosion becomes a problem that will lead to their sense of nationalism. The historical meme comes as entertaiment and history education for society. From that, a question arises. How can historical meme solve the fading sense of generation Z nationalism in the social media era? This reseach will answer it. History learning is needed to overcome the issue of the fading sense of nationalism. Historical knowledge can strengthen one’s devotion for the nation itself through the delivery of historical values. As a generation that is synonymous with technology, conventional solutions are not very effective in instilling historical values.